Evaluation Of Commonly Used Technique For Fabrication Of Provisional Restoration In Fixed Partial Dentures Among Dental Students - An Institution Based Retrospective Study - SRI, DR. HARINI; AHMED, DR. NABEEL; SASANKA, DR. L.KEERTHI (The journal of contemporary issues in business and government, 2021)
Provisional restoration is an integral part of fixed dental prosthesis. The common techniques in fabrication are direct, indirect and indirect-direct. The study was designed to retrospectively evaluate the commonly used technique for fabrication of provisional restoration in fixed partial dentures among dental students and to determine the frequency of use in each sextant. The data was collected from June 2019 to March 2020 at a private dental institution in Chennai and a total of 999 case records of patients who underwent fixed partial denture procedure was obtained. This study reported that 55.1% of temporisation was done using indirect technique, 29.6% used direct technique and 15.2% used direct-indirect technique. Chi-square test was applied to see associations of sextants and techniques used. P value = 0.04 was obtained and was found to be statistically significant. In sextant 1, indirect technique was highly preferred with 51.4%,followed by direct technique with 29.9%. In sextant 2, indirect technique with 53% was preferred followed by direct technique with 33.9%. In sextant 3, 49.2% of indirect technique was observed. In sextant 4 and 5, indirect technique with 62.6% and 55.5% was used respectively. In sextant 6, 61.6% of indirect was highly used. The present study concluded that most of the dental students preferred indirect technique for fabrication of provisional restoration over the other techniques in all the sextants.